PELAKSANAAN HUMAN RELATION DAN PUBLIC RELATION UNTUK MEMBANGUN KERJASAMA DI KECAMATAN CARINGIN - Sukmawati, Shara Ratna; Iskandar, Abubakar; Heryati, Ade (Universitas Djuanda, 2020)
Cooperation has a central position in government organizations as an effort to achieve organizational goals. This study aims to explain the function of the Head to foster human relations and public relations in building internal and external cooperation; Analyzing human relations and public relations must be done in establishing cooperation; Describe the obstacles in fostering human relations public relations in building cooperation. The research design is descriptive correlational, interview data collection techniques, observations documentations data analysis is quantitative and qualitative—the research samples of 35 respondents. The results showed that 40.0 percent were civil servants with a bachelor's degree, while 70.0 percent were honorary employees with high school education. Research shows that 20 percent conduct population administration service activities. As many as 14.3 percent did employee coaching, as many as 5.0 percent set the administration, as much as 45.7 percent typed, 20.0 percent cleaned the room and yard. The integrity level is 3.7 percent. This cohesiveness through the discipline of carrying out the task, As many as 57.1 percent serve the administration, 14.3 percent attend office activities regularly, as many as 57.1 percent say they serve permits. Key words: human relations, public relations, integrity, coaching, cooperation